ECONOMIC ACTIVITY OF THE RURAL POPULATION: A CASE STUDY OF UKRAINE - Oleksandr SHUBALYI; Oksana LIASHENKO; Nadia RUD; Iryna SHUBALA; Inna MYLKO; Nataliia MYKHALCHYNETS (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In the article determined and substantiated that the public opinion that the residents of rural areas, due to less strict observance of the regime of quarantine COVID restrictions on economic activity, lower population density in the settlement network, and technological features of agriculture, suffered smaller losses in terms of employment and income than other strata, turned out to be too optimistic. According to the results of the study, social alienation is increasing as a result of the deterioration of the entire spectrum of social and labour relations. Further research on the chosen subject may be related to strengthening the institutional capacity and financial self-sufficiency of communities due to the decentralization of powers and resources, the transition to a two-level model of inter-budgetary relations, the development of local self-government and changes in the administrative-territorial system, overcoming the social alienation of self-employed persons, provision of force majeure in circumstances similar to the COVID pandemic, economic access to food, health care services, education, culture, transport, and digital infrastructure.